MONUMENTS OF STONE-CUTTING ART AND ARABIC EPIGRAPHY OF THE 14th - 15th CENTURIES FROM THE SETTLEMENT DATSAMAZHE - Mammaev, Misrihan Mammaevic (History, Archeology and Ethnography of the Caucasus, 2018)
The article deals with decoratively finished headstones - monuments of stone-cutting art and Arabic epigraphy of the 14th-15th centuries from Datsamazhe (Kubachinian Dats’amazhe , Dats’amazhila ), now uninhabited small village located 3-4 km north of the old part of the village Kubachi. A comparative study of these monuments and the ones from the villages Kalakoreish and Kubachi has revealed common features as well as differences both in their forms and in decorative finish. Basing on the study, the author comes to the conclusion that medieval stone-cutting art of Kubachi had a significant impact on the development of the art of stone-cutting in Datsamazhe, but the latter developed rather independently and followed its own way. Common features of decorative Arabic inscriptions and floral ornament of the monuments from the villages Datsamazhe and Kubachi testify to the simultaneity of Islamization of the inhabitants of these settlements. However, in Datsamazhe, decorative Arabic calligraphy and floral ornament did not reach the high degree of development and perfection that they achieved in the village Kubachi in the 14th-15th centuries. The author of the article notes that in Early Middle Ages, Datsamazhe was a part of the Zirikhgeran state formation, and later (in the early 17th century), due to some valid reasons (plague epidemic?), its population was greatly reduced, and the remaining small number of inhabitants moved to Kubachi. Being within Zirikhgeran, Datsamazhe maintained close many-sided ties with Kubachi and this fact contributed to its socio-economic and cultural development.